Birth of a naturalist? Nature-related risks and biodiversity loss: Legal implications for the ECB - Marguerite O'Connell (European Central Bank (ECB), 2024)
Recent literature has emphasised that the degradation of nature can have significant implications for central banks in delivering on their mandates. While the primary and most effective actors to address the nature crisis are governments and legislators, central banks will also need to take into account the nature crisis, along with the policies developed and adopted by governments and legislators to address it. This paper offers a first legal assessment of the implications of the nature crisis for the ECB. The paper considers, first, the relevance of nature degradation to the primary objective of maintaining price stability, noting that continued macroeconomic research and assessment will be crucial to ensuring that the ECB properly considers nature-related risk in its monetary policy. Second, the paper outlines that, at the current juncture, it is more difficult to establish that ECB action to address naturerelated risks is necessary to pursue the ECB's secondary objective. Unlike climate action, it is less clear that the prevention of nature degradation constitutes "a general economic policy in the Union". However, this finding does not release the ECB from its other Treaty-based obligations to consider environmental protection in the exercise of its mandate. First, insofar as the protection of nature directly contributes to climate crisis mitigation and adaptation, it can be considered an aspect of that general economic policy in the Union, which the ECB must support under its secondary objective. Second, Articles 7 and 11 TFEU oblige the ECB to ensure consistency with, and to integrate environmental protection requirements - including those relating to nature and biodiversity - into its policies and activities, and to refrain from making decisions that counter these requirements. The paper highlights that as further data become available through the "ecosystem" of Union policies and legislation on nature, it may become easier for the ECB to identify configurations of its monetary policy instrument set that can support the ECB's compliance with Articles 7 and 11 TFEU in a manner that is "equally conducive and not prejudicial to price stability". Third, the prevention of nature degradation may develop into a general economic policy in the Union over time with the adoption of further Union measures to protect nature, including through the implementation of recent international agreements on biodiversity. Finally, the paper offers an overview of how nature degradation and biodiversity loss are already integrated in ECB supervisory policy as a risk component which banks are expected to consider.
Keywords: 330